2004
DOI: 10.1002/j.2050-0416.2004.tb00199.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Effects of Lactic Acid Bacteria in Malting and Brewing with Their Relationships to Antifungal Activity, Mycotoxins and Gushing: A Review

Abstract: Several metabolic properties of lactic acid bacteria (LAB) serve special functions, which directly or indirectly have impact on processes such as improved quality and safety and flavour development in the malting and brewing industry. LAB are widely distributed in nature and in spontaneous fermentations, often they are found to be the dominating microflora resulting in both the inhibition of spoilage bacteria and organisms. This review describes the applications of LAB in malting and brewing. Mycotoxins are na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 148 publications
3
81
0
5
Order By: Relevance
“…Notwithstanding the low levels of mycotoxins found, it is imperative that effective methods be found to suppress microbiological contamination of outdoor malted sorghum. Addition of dilute alkali (NaOH), lactic acid bacteria or yeast culture during steeping could be other alternatives to reduce the microbial load (especially moulds) of sorghum malt 1,11 . of aflatoxins (B 1 , B 2 , G 1 and G 2 ) fumonisins (B 1 and B 2 ), deoxynivalenol (DON), zearalenone (ZEA) and the IC 50 levels of the unmalted sorghum and the top, middle and bottom layers of sorghum malt when germinated at 14-17°C and 18-20°C.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the low levels of mycotoxins found, it is imperative that effective methods be found to suppress microbiological contamination of outdoor malted sorghum. Addition of dilute alkali (NaOH), lactic acid bacteria or yeast culture during steeping could be other alternatives to reduce the microbial load (especially moulds) of sorghum malt 1,11 . of aflatoxins (B 1 , B 2 , G 1 and G 2 ) fumonisins (B 1 and B 2 ), deoxynivalenol (DON), zearalenone (ZEA) and the IC 50 levels of the unmalted sorghum and the top, middle and bottom layers of sorghum malt when germinated at 14-17°C and 18-20°C.…”
Section: Discussionmentioning
confidence: 99%
“…They also contribute to the grain enzyme activity by being important producers of amylolytic, proteolytic and cell wall-degrading enzymes with potentially positive effects on malt characteristics 16,17,26,41,47,50,51,62 . In addition, malt-derived bacteria and fungi with known and carefully selected characteristics can be applied as starter cultures and they offer natural ways to improve the safety and processability of malt 4,31,35 .…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the P. pentosaceus strain used in this study produced such antimicrobial compounds. It is also possible that the P. pentosaceus strain produced antifungal compounds, as it has been shown that numerous LAB exhibit antifungal activities and the active factors have been identified 18 . The inhibition of coliforms by other bacteria can also be attributable to competition for nutrients 13 .…”
Section: Cultures (Code Number) Original Culture Numbers Sourcementioning
confidence: 99%
“…Recently we have shown that these undesirable sorghum malt microflora can be controlled by steeping in dilute NaOH 16 . However, a recent development aims to inhibit the growth of unwanted bacteria and moulds by the addition of desirable microbial cultures as natural biocontrol agents in steeps 18 . Lactic acid bacteria (LAB) 15 and the yeast Geotrichum candidum 4 have been shown to be effective at inhibiting unwanted microorganisms in barley malting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation